2010
DOI: 10.1002/chem.201001875
|View full text |Cite
|
Sign up to set email alerts
|

A Neutral Zwitterionic Molecular Solid

Abstract: We report on the acid ethylenedithiotetrathiafulvaleneamidoglycine (EDT-TTF-CO-NH-CH(2)-CO(2)H; 1; EDT-TTF=ethylenedithiotetrathiafulvalene) and the 1:1 adduct [(EDT-TTF)(·+)-CO-NH-CH(2)-(CO(2))(-)][(EDT-TTF)-CO-NH-CH(2)-(CO(2)H)]·CH(3)OH (2), a new type of hydrogen-bonded, 1:1 acid/zwitterion hybrid embrace of redox peptidics into a two-dimensional architecture, an example of a system deliberately fashioned so that oxidation of π-conjugated cores toward the radical-cation form would interfere with the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…At the moment, the detailed process of the formation of the minimal unit and the electrochemical crystallization is unclear. On the analogy of the formation of phosphonic-acid and amino-acid TTFs 45,46 , however, the process is possibly explained as follows; H 2 Cat-EDT-TTF is diacid. In the presence of bipyridine (see method), the monoanionic (HCat-EDT-TTF) À is generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, the detailed process of the formation of the minimal unit and the electrochemical crystallization is unclear. On the analogy of the formation of phosphonic-acid and amino-acid TTFs 45,46 , however, the process is possibly explained as follows; H 2 Cat-EDT-TTF is diacid. In the presence of bipyridine (see method), the monoanionic (HCat-EDT-TTF) À is generated.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of the molecular conductors based on hydrogen bond-functionalized TTF derivatives have focused on the tuning of the molecular self-assembly and the HOMO/LUMO energy levels 47,48 . In this context, several groups have recently reported that the introduction of the hydrogen bond has another important role, that is, the generation of the charge carriers 46,49 . Besides the carrier generation, our system demonstrates that the symmetric hydrogen bond constructs the new type of the purely organic single-component molecular conductors which are composed of highly symmetric molecular units.…”
Section: Discussionmentioning
confidence: 99%
“…19 We adopted DFT calculations here, but it is known to provide essentially the same results with tight-binding calculations employing the extended Hückel approximation. 23 The anisotropy in the inter-TED transfer integrals is mirrored in the band structure, with a dispersive band along the G to A direction (aaxis), in contrast to a dispersionless one along the G to Z (caxis). The Fermi surface is predominantly one-dimensional (1D) along k a (a-axis) with a large open shape, reecting t a [ t b .…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…Regarding hydrogen bonding, it is well documented that, under favorable circumstances, such bonds are able to cooperate with CT interactions, to modulate the transport properties in the material [29]. The deliberate choice of engaging A and D precursors functionalized by strong hydrogen bond donor/acceptor groups remains a viable strategy in the field of organic conductors [30], and has indeed produced outstanding results [31,32]. Finally, even for complexes close to the neutral state, the spectroscopic determination of δ seems to afford reliable data.…”
Section: Discussionmentioning
confidence: 99%